Nurse's performance in care in Neonatal Intensive Care Units: Integrative literature review (Research, Society and Development, 2021)
The Neonatal Intensive Care Unit (NICU) is designed to care for neonates up to 28 days old who need full-time assistance of high complexity. This study aimed to describe the scientific evidence found in the scientific literature from 2015 to 2019, on the role of nurses in care in neonatal intensive care units. This is a qualitative study, an integrative literature review type that started from the following guiding question: what is the scientific evidence in the literature about the role of nurses in care in neonatal intensive care units, in the period from 2015 to 2019? The databases searched were BDENF, LILACS and SCIELO. The study sample consisted of eleven original articles. For data extraction, Ursi's form was used and for discussion, the Bardin Content Analysis technique. The results were presented and discussed from two thematic categories: “The role of nurses in NICU care” and “The systematization of nursing care (SAE) applied in NICU”. It was concluded that the use of Systematization of Nursing Assistance (SAE) in the NICU is of fundamental importance, since qualified assistance should not be limited to guarantee the survival of the premature, but also plan actions and implement them according to the needs of Care.